Analisis Rasio Arus Kas pada Holding Perkebunan Nusantara PTPN III (Persero) Medan Tahun 2020-2023 - Putri Adelia Siregar; Nadila Safira Girsang; Sifa Aulia Shafira Guechi; Eva Sriwiyanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
PTPN III (Persero) is one of the largest state-owned companies in Indonesia that focuses on the tea, palm oil, coffee and sugar sectors. In the 2020-2023 period, PTPN III faced various global challenges, including commodity price fluctuations, the impact of the COVID-19 pandemic, and environmental and social pressures related to sustainability practices. However, the company managed to carry out a strategic transformation to improve operational, financial and sustainability performance. This cash flow ratio analysis is very important to do considering the importance of understanding the company, especially to know in detail the inflow and outflow or flow of funds to cover the needs and expenses of PTPN III (Persero). The purpose of this study is to provide information on cash inflows and outflows in detail in the 2020-2023 period and focus on the cash flow ratio. This study uses a quantitative descriptive research method whose data source is the 2020-2023 financial statements taken from the official website www.ptpn3.co.id. The aspects taken into account are the ratio of cash flow to current liabilities, capital expenditures, total debt and net profit obtained. The results of the analysis obtained show quite good financial performance movements.